Contribution of anti-BHCG, CK18, hPL and Ki-67 antibodies in the diagnosis of choriocarcinoma in Senegal - Ndiade, Amadou; Dia, Fatou Kiné; Gaye, Abdou Majib; Diallo, Abdou Karim; Diatta, Ange Lucien; Gueye, Mame Venus; Diop, Ndiaga; Diatta, Robert; Diallo, Abdoulaye Sega; Sy, Mama; Thiam, Ibou; Faye, Oumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Gestational choriocarcinoma (GC) is a rare malignant tumour derived from the trophoblast of women of childbearing age. The aim of this study was to determine the contribution of immunohistochemistry in the diagnosis of choriocarcinoma and to evaluate its ability to specify whether or not it is gestational in nature in order to establish a diagnostic algorithm for trophoblastic diseases in general. Methods: This is a retrospective, descriptive, bi-centric study spanning eight (8) years from 1 January 2013 to 31 December 2020. All cases diagnosed on hysterectomy specimens and with a formal conclusion of gestational choriocarcinoma were included. Immunohistochemical staining was performed on formalin-fixed, paraffin-embedded tissue sections using the manual method. We recorded the data collected in Excel 2007 software and the analysis was performed using Epi Info. Results: We collected 25 cases of choriocarcinoma. The average annual frequency was 3.12. The average age of the patients was 38.1±9.7 years (standard deviation). Multiparous women were the most common, accounting for 57.14% of cases. Mixed-site tumours (intracavitary and intramural) were the most common, accounting for 48% of cases. Patients in FIGO stage I accounted for 88% of cases. Immunohistochemistry was performed on 14 samples, revealing 100% positive staining for anti-hCG, CK18 and hPL. Conclusions: Gestational choriocarcinoma (GC) is a proliferation of trophoblasts (cytotrophoblasts and syncytiotrophoblasts). This study demonstrated the indispensability of immunohistochemistry in confirming the diagnosis and in assessing both the progression and therapeutic prognosis of the disease.